PENGARUH PROMOSI DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN DENGAN BRAND IMAGE SEBAGAI VARIABEL MEDIASI - Budianto, Yoseph Pangestu; Budiatmo, Agung (Jurnal Ilmu Administrasi Bisnis, 2020)
The level of product sales / sales turnover can indicate purchasing decisions by consumers. Based on data from CV Champion, the sales turnover of Frisian Flag product sales in the Madiun area fluctuates and never reaches the target. Based on interview resut can be known if there is a problem of public perception of the quality of Frisian Flag products and the lack of promotional activities for Frisian Flag purefarm ready-to-drink milk causes the brand image of Frisian Flag purefarm ready-to-drink is not strong, resulting in the level of sales has not reached the target. This type of research is explanatory research. Sampling using techniques is incidental sampling of 100 respondents. This research uses the IBM SPSS version 16.0 assistance program and analysis for intervention intervention variables. Based on the results of research that shows a positive and significant promotion of brand image, product quality affects positively and significantly on brand image, positive and significant promotion of purchasing decisions, positive and significant product quality on purchasing decisions, positive and significant brand image on purchasing decisions, there is a positive and significant influence on purchasing decisions through brand image, there is a positive and significant influence on purchasing decisions through brand imageSuggestions are given in order to improve purchasing decisions with improvement efforts on promotional variables, product quality and brand image. In the aspect of promotion can increase the frequency of sales promotion, make ads more attractive so that messages can be more talked about by consumers and make consumers interested in buying products. In the aspect of product quality, the company can develop products to provide more nutrition, make packaging shapes more attractive, and provide more attractive and diverse packaging colors. In the aspect of brand image can give a message to consumers who are trying to make consumers loyal to the product.